Transmission characteristics of tuberculosis in the high-TB-burden region of Southwest China - Yang, Xing; Ru, Haohao; Chen, Tao; Chen, Lianyong; Ni, Qinxuan; Yan, Shuangqun; Yang, Rui; Chen, Jinou; Xu, Lin (Frontiers in Public Health, 2025)
BackgroundWhole genome sequencing (WGS) can provide valuable insights into the transmission patterns of Mycobacterium tuberculosis, which can inform effective intervention strategies for controlling tuberculosis (TB) in local areas.MethodsWe conducted a retrospective study using strains isolated from L County between January 2019 and July 2020. Demographic data of patients were retrieved from National Tuberculosis Information Management System. A whole genome sequencing-based clustering analysis was performed to assess the transmission characteristics of pulmonary TB in L County. Univariate and multivariate logistic regression analyses were employed to identify potential risk factors associated with clustering.ResultsA total of 143 strains from 136 confirmed TB cases were available for analysis, among them 74.26% of M. tuberculosis strains belonged to Lineage 2, while Lineage 4 comprised the reminder. Among the pulmonary TB cases, 38.97% (53/136) exhibited genomic-clustered strains (≤12 SNP threshold). Notably, 29 (62.26%) strains belonging to 15 clusters were isolated from the same township, while 10 (18.87%) strains belonging to 5 clusters originated from the same villages. The younger age group (≤44) exhibited a higher risk of clustering (aOR 19.21, 95% CI: 2.37–155.80, p = 0.006). Additionally, 9 (27.27%) drug resistant (DR) strains were identified within cluster, and 4 serial DR strains of 2 patients showed the accumulation of acquired drug resistance.ConclusionA significant proportion of tuberculosis cases in L County are attributed to recent transmission occurring within communities or neighborhoods across townships for both sensitive and drug-resistant TB. These findings suggest that an active case-finding strategy should be implemented in this area to identify patients at the early stages. Furthermore, active screening should not only target key populations such as close household contacts or old population but also extend to all residents over 15 years. Improving chemotherapy treatment quality and patient follow-up is essential in L County.